How is the use of digital dental radiology in a developing country? : an overview of Brazil = ¿Cómo es el uso de la radiología dental digital en un país en vías de desarrollo? : una visión general de Brasil - Moreira Souza, Larissa
The aim of this study was to assess the use of digital dental radiology in Brazil, by focusing on the use of image receptors, imaging exams and digital image enhancement tools, also assessing the methods of professional image transfer. Questionnaires were distributed in person on dental meetings and digitally via messaging (WhatsApp®) and mailings list. The sample of this cross-sectional study consisted of 478 questionnaires. Most participants were woman (n=315, 65.9%), with average age of 33.8±9.2 years. Descriptive and frequency analysis was performed. Chi-square and Fisher's exact tests were used (α=0.05). Most dentists worked at shared dental clinics (34.7%) and use digital image receptors (51.1%), but a representative percentage (48.9%) still exclusively use radiographic films. Photostimulable phosphor plate is the most used digital image receptor. Among extraoral exams, panoramic radiography (PAN) is the most used. Regarding dental specialties, oral radiologists and oral and maxillofacial surgeons mostly use cone-beam computed tomography (p<0.001). Most dentists who use digital systems make use of digital image enhancement tools (87.8%), mainly contrast, zoom, brightness and measurements. The most common method of professional image transfer (professional-professional and professional-patiens) is by email, with few dentists using online app and social media (26%). Therefore, while most Brazilian dentists use digital imaging systems, a significant percentage still exclusively use radiographic films. The most extraoral imaging exams used is PAN. Regarding image enhancement tools, brightness and contrast adjustments, zoom and measurements are the most applied. Finally, dentists generally use email for professional image transfer.